Environment and climate during the Neanderthal-AMH presence in the Garraf Massif mountain range (northeastern Iberia) from the late Middle Pleistocene to Late Pleistocene inferred from small-vertebrate assemblages. (15th July 2022) - López-García, Juan Manuel; Blain, Hugues-Alexandre; Fagoaga, Ana; Bandera, Christian Sánchez; Sanz, Montserrat; Daura, Joan
Abstract: The environmental and climatic evolution of the late Middle Pleistocene to Late Pleistocene of the Garraf Massif (northeastern Iberia) is determined for Marine Isotope Stage 7 (MIS 7) to MIS 3 on the basis of a study of the small-vertebrate (amphibian, squamate reptile, insectivore, bat and rodent) assemblages. This paper provides a synthesis of three previously published and one partially published sets of environmental and climatic data from the Middle to Upper Paleolithic sites of Cova del Rinoceront, Cova del Gegant, Cova del Coll Verdaguer and Terrasses de la Riera dels Canyars, all of which are located in the Garraf Massif mountain range. Using the habitat weighting and mutual ecogeographic range methods to reconstruct the environmental and climatic parameters, the results show great variability in the landscape and climate of the area. However, although the human occupation is not intense in the analyzed sites, the various layers of the sites in which the human presence is relatively more intense coincide with landscapes dominated by woodland formations in mild climatic conditions. A comparison of our results with those from other sites with studies of small vertebrates in Greece, Italy, southern France, and the Iberian Peninsula reveals the same pattern, showing that the hominins that inhabited the western Mediterranean region in the late Middle Pleistocene and Late Pleistocene were closely related to forested areas. Highlights: Synthesis of climatic and environment data for Middle-late to late Pleistocene. Mutual Ecogeographic Range and Habitat weighting used to reconstruct its conditions. Methods applied in the same way for herpetofauna and small mammal's assemblages. Results shows a great variability of the landscape and climate of the studied area.